(untitled) ("Conference on Universal Science Research 2023", 2023)
Elementary education is a crucial period for the academic and cognitive development of children. In recent years, integrating subjects has become a popular approach to ensure the educational process in elementary grades. The integration of math, language, and reading literacy has proven to be effective in enhancing students’ learning outcomes. This article discusses the benefits of subject integration in elementary education and provides an example of how math, language, and reading literacy can be integrated in the classroom. A table is presented to illustrate how a math lesson can be enhanced with reading and language activities. This article discusses the importance of subject integration in elementary education and focuses on the integration of math, language, and reading literacy. The benefits of subject integration in enhancing students’ learning outcomes are presented, and a table is provided to illustrate how a math lesson can be enhanced with reading and language activities.